2004
DOI: 10.1038/sj.bjc.6601967
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic activity of a cyclooxygenase-2 inhibitor

Abstract: Cyclooxygenase-2 (COX-2) expression is increased in breast cancer and surgery has been shown to increase the growth of metastatic tumours. We investigated the effect of selective COX-2 inhibition on the growth of metastases in either an experimental metastasis model or following excision of a murine primary breast tumour. 50 000 4T1 mammary carcinoma cells were injected into the mammary fat pad of female BALB/c mice. When the mean TD reached 870.4 mm, tumours were excised and the mice were randomised into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 48 publications
1
41
0
3
Order By: Relevance
“…Although PGE 2 produced by breast cancer cells has a specific role in bone metastasis, our study does not rule out additional roles of COX-2 in cancer progression, which are not specific to bone metastasis. Role of COX-2 in breast cancer has been demonstrated using several different rodent models, including 7,12-dimethyl-benz(a)anthracene-induced mammary carcinogenesis in rat (Harris et al, 2000), MMTV-COX-2 and MMTV-HER2 transgenic mouse models (Liu et al, 2001;Howe et al, 2002;Chang et al, 2004), MMTV-HER2 transgenic/COX-2 knock-out mouse model (Howe et al, 2005) and xenograft mouse models involving inoculation of cancer cells into fat pad (Connolly et al, 2002;Roche-Nagle et al, 2004). These studies indicate an important role of COX-2 in primary tumor growth, angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although PGE 2 produced by breast cancer cells has a specific role in bone metastasis, our study does not rule out additional roles of COX-2 in cancer progression, which are not specific to bone metastasis. Role of COX-2 in breast cancer has been demonstrated using several different rodent models, including 7,12-dimethyl-benz(a)anthracene-induced mammary carcinogenesis in rat (Harris et al, 2000), MMTV-COX-2 and MMTV-HER2 transgenic mouse models (Liu et al, 2001;Howe et al, 2002;Chang et al, 2004), MMTV-HER2 transgenic/COX-2 knock-out mouse model (Howe et al, 2005) and xenograft mouse models involving inoculation of cancer cells into fat pad (Connolly et al, 2002;Roche-Nagle et al, 2004). These studies indicate an important role of COX-2 in primary tumor growth, angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, COX inhibitors were shown to have a preventive effect on the growth of both the primary tumor and metastases via other mechanisms, such as promotion of tumor apoptosis, 3,4,40,41 reduction in the levels of angiogenic agents, 4,[6][7][8] and diminution of tumor microvascular density. 3 Moreover, a recent study reported that two COX inhibitors, indomethacin and celecoxib, downregulated expression levels of MHC-I molecules on murine mammary tumor cells. Decreased expression of MHC-I is a known triggering signal for NK cells to lyse such tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various tumors have been shown to secrete PGs, 1,2 presumably to escape destruction by suppressing the host's cell-mediated immunity (CMI). Additionally, COX inhibitors were shown to have a preventive effect on the growth of both the primary tumor and metastases via other mechanisms, including the promotion of tumor cell apoptosis, [3][4][5] reduction in the levels of angiogenic agents, [6][7][8] and diminution of tumor microvascular density. 3 As for β-blockers, β1 and β2 adrenoceptors are expressed by several human tumor lines, and catecholamines are potent direct stimulators of migration of various human carcinoma cell types (e.g., colon, breast, and ovary), [9][10][11][12] and of secretion of proangiogenic factors by these tumors (e.g., vascular endothelial growth factor).…”
mentioning
confidence: 99%
“…We focused on the role of COX-2 in metastatic potential by using orthotopic inoculation or injection into the left cardiac ventricle of nude mice with KB/COX-2 and KB/ Neo. Orthotopic inoculation of tumor cells in nude mice is well known as a spontaneous metastasis model (19,20). On the other hand, metastasis to liver by injection of tumor cells to portal vein or spleen (21,22) and metastasis to lung by injection of tumor cells to tail vein (20) are also reported as experimental metastasis models.…”
Section: Discussionmentioning
confidence: 99%
“…Orthotopic inoculation of tumor cells in nude mice is well known as a spontaneous metastasis model (19,20). On the other hand, metastasis to liver by injection of tumor cells to portal vein or spleen (21,22) and metastasis to lung by injection of tumor cells to tail vein (20) are also reported as experimental metastasis models. Although an intra-cardiac injection of tumor cells (23,24) is easier to make metastasis than other models, it is uncommon because of the technical difficulty.…”
Section: Discussionmentioning
confidence: 99%